Yeast communities associated with cacti in Brazil and the description of Kluyveromyces starmeri sp. nov. based on phylogenomic analyses. Issue 12 (8th November 2020) - Freitas, Larissa F.D.; Batista, Thiago M.; Santos, Ana R.O.; Hilário, Heron O.; Moreira, Rennan G.; Franco, Glória R.; Morais, Paula B.; Lachance, Marc‐André; Rosa, Carlos A.
Abstract: Yeast communities associated with cacti were studied in three ecosystems of Southeast, Central and North Brazil. A total of 473 yeast strains belonging to 72 species were isolated from 190 samples collected. Cactophilic yeast species were prevalent in necrotic tissues, flowers, fruits and insects of cacti collected in Southeast and North Brazil. Pichia cactophila, Candida sonorensis and species of the Sporopachydermia complex were the most prevalent cactophilic species in Southeast and Central regions. Kodamaea nitidulidarum, Candida restingae and Wickerhamiella cacticola were frequently associated with cactus flowers and fruits. The diversity of yeasts associated with the substrates studied was high. Twenty‐one novel species were found. One is described here as Kluyveromyces starmeri sp. nov. based on 21 isolates obtained from necrotic tissues, flowers, fruits and associated insects of the columnar cacti Cereus saddianus, Micranthocereus dolichospermaticus and Pilosocereus arrabidae in two different ecosystems in Brazil. Phylogenetic analyses of sequences encoding the gene of the small subunit (SSU) rRNA gene, the internal transcribed spacer, the 5.8S rRNA gene and the D1/D2 domains of the large subunit (LSU) rRNA showed that the species is related to Kluyveromyces dobzhanskii, Kluyveromyces lactis and Kluyveromyces marxianus . Phylogenomic analyses based on 1264 conserved genes shared among the new species and 19 other members of the Saccharomycetaceae confirmed this phylogenetic relationship. The holotype is K. starmeri sp. nov. CBS 16103 T (=UFMG‐CM‐Y3682 T ). The Mycobank number is MB 836817.